Bone morphogenetic protein 4 in perivascular adipose tissue ameliorates hypertension through regulation of angiotensinogen - Mu, Wen-Juan; Song, Yan-Jue; Yang, Li-Jie; Qian, Shu-Wen; Yang, Qi-Qi; Liu, Yang; Tang, Qi-Qun; Tang, Yan (Frontiers in Cardiovascular Medicine, 2022)
Background: PVAT (perivascular adipose tissue), an active endocrine organ, exerts direct effect on vascular tone through paracrine. Activation of PVAT metabolism plays an inhibitory role in atherosclerosis via secreting relaxing factors. The present studies were designed to investigate the role of PVAT metabolism in regulation of hypertension. Methods: ApoE (apolipoprotein E) knockout mice with BMP4 knockout in adipose tissue or brown adipose tissue (aP2-DKO or UCP1-DKO, respectively) were used for exploring the role of impaired PVAT metabolism in hypertension. Vascular function was assessed using wire myography. The potential regulatory factor of vascular function was explored using qPCR and ELISA and further confirmed in perivascular fat cell line. Results: Knockout of BMP4 either in adipose tissue or specifically in BAT aggravates high-fat diet (HFD, 40% fat)-induced hypertension and endothelial dysfunction in ApoE−/− mice. In the meanwhile, deficiency of BMP4 also aggravates Ang Ⅱ (angiotensin Ⅱ) -induced hypertension and vascular remodeling in ApoE−/− mice. Moreover, deficiency of BMP4 inhibits NO release and induces ROS production. In vitro system, aortic rings pretreated with PVAT extracts from BMP4-DKO mice showed increased vasoconstriction and reduced endothelial-dependent relaxation compared with the controls. We further demonstrated that PVAT of BMP4-DKO mice expressed higher level of angiotensinogen (AGT) and Ang Ⅱ compared with the controls. Conclusion: Impaired PVAT metabolism aggravates hypertension, and this effect is dependent on the activation of local renin-angiotensin-aldosterone system (RAAS). The results of this study first demonstrate the regulatory role of PVAT metabolism in hypertension.